STUDI META ANALISIS PENGARUH KEPEMIMPINAN TERHADAP BUDAYA ORGANISASI PADA LEMBAGA PENDIDIKAN DI INDONESIA - Dedi Purwana ES. (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2016)
The studyaims to examine the influence of leadership on organizational culture at Indonesian education institutions.It was conducted from April to October 2015. Meta-analysis approach was used to study of the 12 research publications related to the examined variables.These correlational researches were conducted in 2010-2015. The data was retrieved from two public higher education libraries in Indonesia. The study concluded that leadership had directy effect on organizational culture. The result of meta-analysis indicates that average of correlation coefficient ( ) is0,573 with standard deviation equals 0,101565 and corrected correlation (rc) values0,623. The differences of the 12 correlations coefficient are caused by sampling error (Ã³2e) = 0,006749 with variance estimation (ï³2ï²) = 0,01061.